LCFA accumulation and biodegradation during anaerobic discontinuous treatment of an oleate-rich wastewater - Cavaleiro, A. J. (2007)
The dynamics of medium and long-chain fatty acids (LCFA) accumulation and biodegradation was studied during the anaerobic treatment of an oleate-rich wastewater. This treatment was made in an upflow sludge bed reactor operated in cycles during 213 days. Five cycles were performed, each one with a feeding phase in continuous and a reaction phase in batch. Saturated and unsaturated fatty acids from C6 to C18 were extracted and analyzed by gas chromatography on biomass samples collected at different key moments of the reactor operation. These biomass samples were also incubated in batch assays and methane production from the accumulated substrate was followed. LCFA accumulated onto the sludge during the first two cycles, reaching a maximum value of 1.7 gCOD-LCFA.gVSˉ¹. Palmitate and stearate were the dominant intermediates quantified, approximately in equal quantities. On the subsequent cycles only residual amounts of LCFA were detected. Methane production on batch assays was higher than expected from the LCFA accumulated, suggesting that other substrates could also be entrapped with the sludge. The results show that during the first two cycles a specialized microbial consortium developed, able to treat oleate-rich wastewaters.